Megan Branigan: capstone - Branigan, Megan, artist (Colorado State University. Libraries, 2014)
The artist's statement: In this day and age of growing technology, we are finding more and more ways to make things easier to achieve, create, and master, including different types of jobs, everyday tasks, and even more so, new ways to create art. People are getting so easily enamored and obsessed with all these new kinds of art that they are starting to forget where it all began. I am on an ever-‐ lasting mission to change that. Unlike a lot of artists my age, and sometimes even older, I strive to never use an image that was already created by the hand of another, whether it's a drawing, a photo, or other form of media. Usually, with my creations, everything the viewer will see in front of them was originally hand-‐ drawn, going from my mind, to a pencil, and to the piece of paper in front of me. I wish to create art that will bring people back to when times were simpler, and when we were still making art 'for art's sake'. As incredibly unlikely as it probably seems, pieces of art come to me instantly. Others brainstorm for days, sometimes even weeks to figure out what they are doing when given a topic to work with, but with a few simple words, and a brief description of what someone wants to see, the ideas come flowing into my brain no problem. I have made it an objective to, generally, create art that is distinctive, and even more so, if I execute it properly, will get people to think about it, even if only a little. Over time, I have slowly forged my own style while admiring some of the great artists of my childhood along the way, including: Bruce Timm, Craig McCracken, and Hayao Miyazaki. Like them, I want my work to inspire both children and adults alike to make their own creations and bring them to life. Their work is tremendous, and does not need to be incredibly flashy to make an impact, just like I hope my work will do. When I get older and look back at a life of creating art, I hope I will take great pride and pleasure in my passion for originality and the use of the magnificent world of imagination to bring life to my mind's vivid thoughts and creations.
Capstone contains the artist's statement, a list of works, and images of works.
Colorado State University Art Department capstone project